GCN: a gaseous Galactic halo stream? - Jin, Shoko (Monthly notices of the Royal Astronomical Society, 2010)
We show that a string of H i clouds that form part of the high-velocity cloud complex known as GCN is a probable gaseous stream extending over more than 50° in the Galactic halo. The radial velocity gradient along the stream is used to deduce transverse velocities as a function of distance, enabling a family of orbits to be computed. We find that a direction of motion towards the Galactic disc coupled with a mid-stream distance of ∼20 kpc provides a good match to the observed sky positions and radial velocities of the H i clouds comprising the stream. With an estimated mass of 105 M⊙, its progenitor is likely to be a dwarf galaxy. However, no stellar counterpart has been found amongst the currently known Galactic dwarf spheroidal galaxies or stellar streams and the exact origin of the stream is therefore currently unknown.
Gesehen am 28.08.2023